FOSTERING DIVERSITY, EQUITY, AND INCLUSION: HR’S ROLE IN BUILDING INCLUSIVE ORGANIZATIONAL CULTURES - Kulkarni, Mihika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The emphasis on Diversity, Equity, and Inclusion (DEI) has significantly increased in recent years, as organizations understand the importance of establishing inclusive cultures. This paper investigates the vital role that Human Resources (HR) plays in promoting DEI within companies. Through a review of existing literature and primary research, this study looks at how HR policies and practices affect inclusivity, employee engagement, and overall organizational performance. The results indicate that a proactive HR strategy greatly enhances DEI initiatives, resulting in better employee well-being and greater innovation. The paper concludes with practical strategies for HR professionals to foster and maintain inclusive organizational cultures.